A crucial arginine residue is required for a conformational switch in NifL to regulate nitrogen fixation in Azotobacter vinelandii - Martinez-Argudo, Isabel (National Academy of Sciences, 2004)
NifL is an antiactivator that tightly regulates transcription of genes required for nitrogen fixation in Azotobacter vinelandii by controlling the activity of its partner protein NifA, a member of the family of σ(54)-dependent transcriptional activators. Although the C-terminal region of A. vinelandii NifL shows homology to the transmitter domains of histidine protein kinases, signal transduction between NifL and NifA is conveyed by means of protein-protein interactions rather than by phosphorylation. Binding of the ligand 2-oxoglutarate to NifA plays a crucial role in preventing inhibition by NifL under conditions appropriate for nitrogen fixation. We have used a suppressor screen to identify a critical arginine residue (R306) in NifL that is required to release NifA from inhibition under appropriate environmental conditions. Amino acid substitutions at position 306 result in constitutive inhibition of NifA activity by NifL, thus preventing nitrogen fixation. Biochemical studies with one of the mutant proteins demonstrate that the substitution alters the conformation of NifL significantly and prevents the response of NifA to 2-oxoglutarate. We propose that arginine 306 is critical for the propagation of signals perceived by A. vinelandii NifL in response to the redox and fixed-nitrogen status and is required for a conformational switch that inactivates the inhibitory function of NifL under conditions appropriate for nitrogen fixation.